THE IMPLEMENTATION OF COOPERATIVE LEARNING METHOD IN TEACHING ENGLISH AT INDONESIAN JUNIOR HIGH SCHOOL - Raharjo, Moelyo; Salija, Kisman; Hidayahni Amin, Fatimah (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
This research explores the implementation of the cooperative learning method in teaching speaking at a Junior High School in Takalar, Indonesia. Employing a qualitative research design, data was gathered through observation, interviews, and documents involving six students and one teacher. The research addresses three primary questions: the teacher’s implementation of the cooperative learning method, the teacher’s perception of this method, and the students’ perceptions. The findings reveal that the teacher implemented the cooperative learning method through a structured approach over four weeks. 1)The implementation of cooperative learning methods in teaching speaking were divided into opening activities, main activities, and closing activities. 2) Teacher's perception towards the implementation of cooperative learning method in teaching speaking found giving positive perception. 3) Students' perception towards the implementation of cooperative learning method in learning speaking found five students giving positive perception and only one student giving negative perception.